Elizabeth : the golden age [videorecording (DVD)] - Kapur, Shekhar, 1945-; Blanchett, Cate, 1969-; Rush, Geoffrey, 1951-; Mollà, Jordi (Universal Studios Home Entertainment, 2008)
Queen Elizabeth's reign is threatened by familial betrayal and Spain's invading army. She and her shrewd advisor must act to safeguard to the lives of her people. When the dashing seafarer, Walter Raleigh, captures her heart, Elizabeth is forced to make her most tragic sacrifice for the good of her country. A tale of one woman's crusade to control her love, destroy her enemies and secure her position as a beloved icon of the western world.